Erratum: MIGUEL A. MONNÉ & MARCELA L. MONNÉ (2012) New species of Acanthocinini from South America (Coleoptera: Cerambycidae). Zootaxa, 3478, 192–200. - Monné, Miguel A.; Monné, Marcela L. (Zootaxa, 2012)
(Erratum)